Conductor-Insulator Quantum Phase Transitions 2012
DOI: 10.1093/acprof:oso/9780199592593.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Dynamics of Electrons Near the Metal–Insulator Transition

Abstract: PrefaceThis review first describes the evidence that strongly suggests the existence of the metal-insulator transition (MIT) in a two-dimensional electron system in Si regardless of the amount of disorder. Extensive studies of the charge dynamics demonstrate that this transition is closely related to the glassy freezing of electrons as temperature T → 0. Similarities to the behavior of three-dimensional materials raise the intriguing possibility that such correlated dynamics might be a universal feature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 122 publications
(314 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, many novel materials behave effectively as two-dimensional (2D) systems, but the 2D MIT remains one of the most fundamental open problems in condensed matter science. [1][2][3][4][5][6][7] In fact, the 2D electron system in Si MOSFETs is the only system in which detailed and comprehensive investigations of this quantum (i.e. T = 0) phase transition have been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many novel materials behave effectively as two-dimensional (2D) systems, but the 2D MIT remains one of the most fundamental open problems in condensed matter science. [1][2][3][4][5][6][7] In fact, the 2D electron system in Si MOSFETs is the only system in which detailed and comprehensive investigations of this quantum (i.e. T = 0) phase transition have been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, the microscopic origin of the metal–insulator transition (MIT) in most materials of interest is not well understood. Furthermore, many novel materials behave effectively as two-dimensional (2D) systems, but the 2D MIT remains one of the most fundamental open problems in condensed matter science. In fact, the 2D electron system in Si MOSFETs is the only system in which detailed and comprehensive investigations of this quantum (i.e., T = 0) phase transition have been carried out so far. On the basis of Si MOSFET studies, it has been suggested that there are three universality classes for the 2D MIT. , However, to test the universality of the observed behaviors, it is necessary to probe 2D systems in other types of materials and, in particular, beyond conventional semiconductor heterostructures.…”
Section: Introductionmentioning
confidence: 99%